COVID-19 Pandemic and Teaching and Learning: A Literature Review - Irshad Ahmad Reshi; Khanrafiq; Wanihaya (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Nearly 1.7 billion students in more than 200 nations have been impacted by the COVID-19 epidemic, making it the biggest interruption to education systems in human history. More than 94% of the world's student population has been affected by the closure of schools, institutions, and other learning venues. Because of this, our entire way of life has been drastically altered. Policy decisions that limit people's freedom of movement and separate them from their communities have disrupted long-standing methods of teaching and learning. There are several new standard operating procedures that must be implemented before schools can reopen after restrictions have been lifted. Many scholars have quickly disseminated their findings on various forms of instruction since the COVID-19 epidemic. Face-to-face instruction has been phased out by a number of educational institutions. Some worry that the 2020–2021 school years will be lost forever. It is urgent that new approaches to teaching and testing be developed and put into practice. The COVID-19 epidemic has given us the chance to lay the groundwork for the widespread use of online education. This article's goal is to provide a detailed assessment on how the COVID-19 epidemic has affected online education and to offer suggestions for moving forward.